Improving Sharia Risk Compliance: Proposing Daily Index for Mudharaba Contract in Islamic Banks in Indonesia - Laode Hasahu; Anita Priantina; Dewi Febriani (Tazkia Islamic Finance and Business Review, 2012)
Objective – The objective of this paper is to analyze the profit distribution method applied in Islamic banks in Indonesia and to propose better method in order to improve sharia risk compliance.Methods – Employing a descriptive quantitative method and literature review. This paper evaluate weaknesses of the current profit distribution method and proposes daily revenue index to solve the problems arising from using current method which is unfairness between bank and customers.Results – By the two current profit distribution methods which use monthly revenue index calculated only at the end of the month, there are potential injustices occur. Therefore, instead of using monthly index, daily index is proposed. There are two steps in calculating profit distribution by using daily revenue index: (1) Accumulating Source of Fund (SoF), Reserve Requirement (RR), and Source of Fund after Reserve Requirement (SoFaRR), and (2) Determining Average Financing (AF), Revenue Index (RI), Cost Index (CI), Revenue Sharing Index (RSI), and Profit Sharing Index (PSI).Conclusion - Daily revenue index will solve the unfairness problems arise from current profit distribution method applied in Islamic banks. Daily revenue index is also applicable if Islamic banks apply profit and loss sharing instead of revenue sharing.